2009
DOI: 10.2174/092986709789057635
|View full text |Cite
|
Sign up to set email alerts
|

Substrates, Inducers, Inhibitors and Structure-Activity Relationships of Human Cytochrome P450 2C9 and Implications in Drug Development

Abstract: Cytochrome P450 2C9 (CYP2C9) is one of the most abundant CYP enzymes in the human liver. CYP2C9 metabolizes more than 100 therapeutic drugs, including tolbutamide, glyburide, diclofenac, celecoxib, torasemide, phenytoin losartan, and S-warfarin). Some natural and herbal compounds are also metabolized by CYP2C9, probably leading to the formation of toxic metabolites. CYP2C9 also plays a role in the metabolism of several endogenous compounds such as steroids, melatonin, retinoids and arachidonic acid. Many CYP2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 1,225 publications
(1,828 reference statements)
1
82
2
5
Order By: Relevance
“…CYP2C9 catalyses the oxidation of clinically important drugs including phenytoin, tolbutamide, warfarin, and a large number of nonsteroidal anti-inflammatory drugs (Miners and Birkett, 1998;Zhou et al, 2009b;Kesavan et al, 2010). Presently, 34 different CYP2C9 allelic variants have been identified (http://www.cypalleles.ki.se/cyp2c9.htm, January 2009).…”
Section: Introductionmentioning
confidence: 99%
“…CYP2C9 catalyses the oxidation of clinically important drugs including phenytoin, tolbutamide, warfarin, and a large number of nonsteroidal anti-inflammatory drugs (Miners and Birkett, 1998;Zhou et al, 2009b;Kesavan et al, 2010). Presently, 34 different CYP2C9 allelic variants have been identified (http://www.cypalleles.ki.se/cyp2c9.htm, January 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation by P450s can lead to toxic products, but, on the other hand, local activation of, e.g., anticancer prodrugs by P450s to lethal intracellular toxins at the site of the tumor is an important strategy (1). Drug compounds can induce P450 expression but can also inhibit them in various ways (2)(3)(4). The metabolic clearance of most drugs depends on P450s, and they have been implicated in a large number of drug-drug interactions (5,6), which can result in fatalities (7,8).…”
mentioning
confidence: 99%
“…24 As stated earlier, celecoxib is extensively metabolized by CYP2C9. 25 An in vitro study utilizing human liver microsomes in addition to yeast microsomes expressing a number of CYP polymorphisms showed that CYP2C9*3 had a lower intrinsic clearance of celecoxib when compared with the wild-type CYP2C9*1 samples. 26 There are conflicting results about whether CYP2C9*2 has a significant decrease in intrinsic clearance.…”
Section: Diaryl Heterocyclic Cox-2-selective Inhibitorsmentioning
confidence: 99%
“…22 Naproxen sodium is metabolized by the liver enzyme CYP2C9 forming 6-desmethylnaproxen. 25 Like flurbiprofen, the CYP2C9*3 and CYP2C9*5 alleles show a lower clearance when compared with the wild-type CYP2C9*1. 18 However, another study assessed the role of CYP2C9 in the overall clearance of naproxen and concluded that CYP2C9 played a minor role in naproxen clearance, suggesting that pharmacogenetic differences would not be clinically significant if compromised CYP2C9 activity was possessed by a patient taking this medication.…”
Section: Propionic Acid Derivativesmentioning
confidence: 99%